CELEBRITIES AS LEGISLATORS IN INDONESIA: A CORPUS-ASSISTED DISCOURSE ANALYSIS OF PUBLIC NARRATIVES ON SOCIAL MEDIA X - Nasyaya, Annada; Musdalifah, Farisha Sestri; Yogsunandar, Harry (Universitas Negeri Yogyakarta, 2025)
This study explores public responses to celebrities elected as members of the Indonesian House of Representatives for the 2019–2024 term. The study adopts a corpus-assisted discourse analysis (CADS), a methodological approach that combines corpus linguistics and critical discourse analysis to identify dominant patterns, lexical features, and thematic structures in large-scale textual data. A dataset of 26,120 tweets mentioning 14 celebrity legislators was collected through data scraping from October 2019 to June 2024. The data were processed using Google Colaboratory and R Studio for cleaning, and analyzed with AntConc to identify linguistic patterns, keywords, and thematic categories. The analysis reveals that discussions are concentrated on a few prominent figures—namely Krisdayanti, Rano Karno, and Eko Patrio highlighting themes such as personal background, lifestyle, legislative activity, and public image. Findings show that public opinion is polarized, with both positive and critical evaluations of celebrity-legislators’ effectiveness and authenticity. This study also highlights the intersection between entertainment and formal politics in Indonesia. Policy implications highlight the need for capacity-building and transparency mechanisms to support celebrity politicians in promoting effective public communication and democratic accountability.